A study on syntactic and semantic features of English weather proverbs and idioms denoting weather with reference to the Vietnamese equivalents / Nguyễn Thị Bích Huệ; NHDKH Dr. NGUYEN DANG SUU. - Nguyễn, Thị Bích Huệ
Syntactic features: there are more differences than similarities between EWPI and VWPI. EWPI display four sentence types: simple sentences, compound sentences, complex sentences and irregular sentences; meanwhile, there are only three sentence types used in VWPI: simple sentences, compound sentences and complex sentences; irregular sentences cannot be found in VWPI in my data. Semantic features, the thesis deals with the two semantic fields: anticipating weather changes and the weather’s influence on human life. The anticipation of weather changes is categorized into two groups: means of anticipating weather changes and anticipated weather conditions. Meanwhile, the weather’s influence on human life is divided into two groups: the weather’s influence on production and the weather’s influence on human health.